2010
DOI: 10.3346/jkms.2010.25.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status of Vitamin D and the Effect of Vitamin D Supplementation in Korean Breast-fed Infants

Abstract: We investigated the vitamin D status and the effect of vitamin D supplementation in Korean breast-fed infants. The healthy term newborns were divided into 3 groups; A, formula-fed; B, breast-fed only; S, breast-fed with vitamin D supplementation. We measured serum concentrations of vitamin D (25OHD3), calcium (Ca), phosphorus (P), alkaline phosphatase (AP), intact parathyroid hormone (iPTH) and bone mineral density (BMD) at 6 and 12 months of age. Using questionnaires, average duration of sun-light exposure an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 22 publications
(31 reference statements)
4
25
1
2
Order By: Relevance
“…They reported that the release of proinflammatory cytokines such as TNFα by immunocompetent cells does not differ significantly in breastfed and formula-fed infants, despite differences in cell membrane fatty acid composition (20). Although the levels of serum Ca 2+ , P concentrations and the activity of ALP in the present study confirmed the finding of the others, some investigator reported that there are no statistically significant differences among breast and formula feeding infants in serum Ca, P, and ALP at birth, and also serum Ca and ALP were not different in the two groups at 6 and 12 months of ages (21, 22). Further studies with a larger sample size are required to confirm these findings.…”
Section: Discussionsupporting
confidence: 86%
“…They reported that the release of proinflammatory cytokines such as TNFα by immunocompetent cells does not differ significantly in breastfed and formula-fed infants, despite differences in cell membrane fatty acid composition (20). Although the levels of serum Ca 2+ , P concentrations and the activity of ALP in the present study confirmed the finding of the others, some investigator reported that there are no statistically significant differences among breast and formula feeding infants in serum Ca, P, and ALP at birth, and also serum Ca and ALP were not different in the two groups at 6 and 12 months of ages (21, 22). Further studies with a larger sample size are required to confirm these findings.…”
Section: Discussionsupporting
confidence: 86%
“…Values of serum 25OHD less than 20 ng/ml [21][22][23][24] and less than 10 ng/ml [12,[25][26][27][28][29] were taken as cut-off thresholds indicative of vitamin D deficiency.…”
Section: Definitionsmentioning
confidence: 99%
“…Four intervention studies of vitamin D supplementation in breast-fed infants have reported outcomes related to bone mineralisation. In all but one study [84], serum 25(OH)D was greater in the supplemented infants, but no differences in BMC or BMD were identified at 3 months [85], 6 months [86] or 12 months [86,87] of age. In one study a significantly greater distal radius BMC measured by single photon absorptiometry was measured in the supplemented infants at 12 weeks of age, but not at 26 weeks of age [84].…”
Section: Infant Vitamin D Status and Bmdmentioning
confidence: 99%